Characteristiscs of Syphilis Patient at Dermatology and Venereology Polyclinic - Tanoto, Suma Pratiwi; Permana, Aditya; Suyanto, Firly Clarissa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: In 2022, the United States reported 207,255 syphilis cases, marking a 17.3% increase from 2021, and the highest incidence since 1950.  In Indonesia, early and late-stage syphilis cases reached 2,981 and 1,144 cases respectively in the first quarter of 2023. Purpose: This study aims to describe the characteristics of syphilis patients at the Dermatology and Venereology Polyclinic at Prof. Dr. I.G.N.G Ngoerah General Hospital. Methods: A retrospective descriptive study was conducted using secondary data from medical records of syphilis patients between January 2021 to December 2023. Data were obtained from the Sexually Transmitted Infection divisions. The study examined patient characteristics, including age, sex, occupation, comorbid conditions, syphilis stage, HIV status, sexual orientation, and sexual behaviour. Result: Out of 346 cases, the highest new syphilis cases recorded in 2021 (133 cases, 86%). The majority of patients were diagnosed with late latent syphilis (211 cases, 61%). The majority of patients were male (59%). The most affected age group was 25–44 years (174 cases, 51%). Private-sector employees represented the largest occupational group (118 cases, 34%). The most common comorbid condition was condyloma acuminatum, 45 patients (50%). In terms of sexual behavior, 62 patients (36%) engaged in receptive sexual activity. Heterosexual orientation was the most frequently reported (176 cases, 51%). Additionally, 205 patients (60%) were HIV-positive. Conclusion: This study has provided important characteristic data in mapping the population to the stages of syphilis, especially in the Bali region.